2008
DOI: 10.1177/0047287506303981
|View full text |Cite
|
Sign up to set email alerts
|

Culinary Tourism Supply Chains: A Preliminary Examination

Abstract: This article begins by defining culinary tourism as any tourism experience in which one learns about, appreciates, or consumes branded local culinary resources. The centrality of local ingredients and culinary resources to the culinary tourism experience means that an understanding of the issues and structures associated with accessing those resources can contribute to a deeper understanding of culinary tourism as a product and its linkages to other sectors of the economy. Supply chain theory is introduced and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
0
24

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(152 citation statements)
references
References 16 publications
3
125
0
24
Order By: Relevance
“…Therefore it is a kind of tourism that connects travel, leisure, and food (Boniface, 2003;Smith & Xiao, 2008) and provides travelers with memorable experiences (Hashimoto & Telfer, 2006;Okumus, Kock, Scantbury, & Okumus, 2013).…”
Section: Literature Review Food Tourism and Food Marketsmentioning
confidence: 99%
“…Therefore it is a kind of tourism that connects travel, leisure, and food (Boniface, 2003;Smith & Xiao, 2008) and provides travelers with memorable experiences (Hashimoto & Telfer, 2006;Okumus, Kock, Scantbury, & Okumus, 2013).…”
Section: Literature Review Food Tourism and Food Marketsmentioning
confidence: 99%
“…There are four types of gastronomic tourism resources (Smith and Xiao, 2008): facilities (buildings, land, and roots), activities (consumption types, gastronomic tours, and trainings), events (consumer shows, festivals) and organizations (associations). The fact that a destination has the resources to supply it is not a reliable criterion for its development in terms of gastronomic tourism alone.…”
Section: Extensive Summarymentioning
confidence: 99%
“…In addition, it has been the subject of studies to go beyond just the definition, and some problems have been sought in related works. For example, after the work of Coveney and Santich (1997), Smith and Xiao (2008) also worked to solve the problems in the supply chain and in this way they tried to solve the problems that stakeholders have in the food production and distribution methods.…”
Section: Extensive Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Smith & Xiao suggested that tourism distribution channels could be regarded as different presentation of tourism supply chain for invisibility and complexity of tourism products [6]. Pearce, from view of tourists, adopted field research method to study distribution channels met by tourists in Rotorua and Wellington of New Zealand, which provided a new perspective for improvement of tourism distribution channels [7].…”
Section: Status Of Research On Tourism Distribution Channelmentioning
confidence: 99%